2010
DOI: 10.4269/ajtmh.2010.09-0197
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Rickettsia rickettsii and Occurrence of Other Spotted Fever Group Rickettsiae in Ticks from Tennessee

Abstract: Rocky Mountain spotted fever (RMSF) is the most common tick-borne illness in Tennessee. Little is known about the occurrence of R. rickettsii, the causative agent, in ticks in Tennessee. To better understand the prevalence and distribution of rickettsial agents in ticks, we tested 1,265 Amblyomma, Dermacentor, and Ixodes adult and nymphal ticks. Additionally, we tested 231 Amblyomma americanum larvae. Ticks were collected from 49 counties from humans, wild animals, domestic canines, and flannel drags. Spotted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
53
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 31 publications
5
53
1
Order By: Relevance
“…This bacterium seems to have a wide distribution and has been found infecting various species of ticks across various countries in the Americas: Unites States (STROMDAHL et al, 2008;JIANG et al, 2010;MONCAYO et al, 2010;TROUT et al, 2010;, Honduras (NOVAKOVA et al, 2015), Costa Rica (HUN et al, 2011;OGRZEWALSKA et al, 2015), Panama (BERMUDEZ et al, 2011), French Guyana (PAROLA et al, 2007 and Argentina (LABRUNA et al, 2007c).…”
Section: Rickettsia Species Found In Ticks Parasitizing Birds In Brazilmentioning
confidence: 99%
“…This bacterium seems to have a wide distribution and has been found infecting various species of ticks across various countries in the Americas: Unites States (STROMDAHL et al, 2008;JIANG et al, 2010;MONCAYO et al, 2010;TROUT et al, 2010;, Honduras (NOVAKOVA et al, 2015), Costa Rica (HUN et al, 2011;OGRZEWALSKA et al, 2015), Panama (BERMUDEZ et al, 2011), French Guyana (PAROLA et al, 2007 and Argentina (LABRUNA et al, 2007c).…”
Section: Rickettsia Species Found In Ticks Parasitizing Birds In Brazilmentioning
confidence: 99%
“…10 Amblyomma americanum ticks have been found to be infected with R. amblyommii in the southeastern United States and in the lower midwestern and coastal New England regions. [11][12][13][14] Rickettsia parkeri, another SFGR, has also been associated with human illness. The principle vector for R. parkeri is Amblyomma maculatum, the Gulf Coast tick.…”
Section: Introductionmentioning
confidence: 99%
“…16 Furthermore, tick surveys conducted in Tennessee have not detected R. rickettsii but R. amblyommii, R. parkeri, and R. montanensis were commonly found. 5,10 Similarly, tick surveys conducted in neighboring states in the southeastern region revealed the same pattern of the predominance of R. amblyommii in Amblyomma americanum ticks, the most ubiquitous and aggressive tick species in this region. 8,15,22,23 Finally, an Oklahoma study in canines used as sentinels for rickettsial diseases, also showed similar results.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous tick surveys, including those conducted in Tennessee, have shown the absence of R. rickettsii but the presence of other SFG Rickettsia such as Rickettsia amblyommii, Rickettsia Parkeri, and Rickettsia montanensis. [5][6][7][8][9][10] The contradicting reports of increasing incidence of SFG rickettsiosis (including RMSF) and the rarity of R. rickettsii in ticks raise the likelihood that other SFG rickettsiae species are contributing to this increase in incidence. Previous studies have demonstrated evidence for infection with other less pathogenic SFG rickettsiae species that clinically resemble RMSF.…”
Section: Introductionmentioning
confidence: 80%